Pelatihan Pembuatan Pupuk Organik Cair dan Eco Enzym untuk Pemeliharaan Anggrek di Desa Sabuhur, Kalimantan Selatan - Istikowati, Wiwin Tyas; Sunardi, Sunardi; Abidin, Zainal; Surya, Adhi; Fauzan, Akhmad; Saputra, Debi Imam; Norhidayah, Anisa; Hadijah, Siti; Sari, Evita; Hidayanti, Nurul; Rahmawati, Risma (Kayuh Baimbai: Jurnal Pengabdian Masyarakat, 2024)
This service activity aims to train Sabuhur villagers in making liquid fertilizer for orchid care. Sabuhur villagers are members of KTH Amabilis Lestari and KTH Pantai Baru, who are assisted by the South Kalimantan BKSDA in an effort to conserve Kalimantan orchids.  They are under the guidance of South Kalimantan Natural Resources Conservation Center which is active in saving local Kalimantan orchids. The conservation activity by carried out the orchids from the forest around Sabuhur village which will be converted into plantation areas or mining land. The rescue activities were also carried out after a storm caused many trees had fallen, where the orchids were lived. The orchids are maintained around their homes using simple methods without fertilizer application regularly due to the high cost of the fertilizer. This project teaches orchid caretakers how to generate organic fertilizer from household garbage. Lambung Mangkurat University's community service team collaborated with Muhammad Al Banjari Islamic University of South Kalimantan and the Natural Resources Conservation Agency of South Kalimantan to provide training on the production of liquid organic fertilizer and eco-enzymes. From the activity carried out, the participant gained new knowledge and improve the skills